ANALISIS KONTRASTIF AFIKSASI VERBA BAHASA JAWA DAN BAHASA INDONESIA DALAM ALBUM POP JAWA GUYON WATON 2019-2021 - Nadea Juliana; Herlin Sulistyo Rini; Odien Rosidin (Jurnal Bastra (Bahasa dan Sastra), 2026)
This research describe the similarities and differences of verb affixation in Javanese and Indonesian through song lyrics in the Javanese pop album Guyon Waton (2019-2021). The main focus is on prefixes, suffixes, and confixes. Music was chosen as the object because it functions as a medium of expression and Guyon Waton represents the innovation of the younger generation through the fusion of Javanese culture and modern style. This research uses descriptive qualitative method with listening technique, in which the researcher only acts as an observer without direct interaction. The analysis was conducted through a contrastive approach and morphological theory to identify the forms of affixation that appear based on the similarities and differences between the two languages. The findings reveal 21 similarities and 10 differences in the use of verb affixation between Javanese and Indonesian.